APPLICATION OF UV-SPECTROPHOTOMETRY FOR THE QUANTITATIVE DETERMINATION OF CAPTOPRIL IN DRUG - Yu. V. Monaykina; S. O. Vasjuk; Almohamad Jumaa Abdullah; V. V. Gladyshev (Zaporozhye State Medical University, 2015)
Introduction. In this paper the simple, rapid and sensitive assay method for the quantitative determination of captopril in two new pharmaceutical formulations (suppositories and nasal gel) is proposed. Analysis was performed directly by using zero-order UV spectrophotometry. It is known from the special literature that the chromatographic techniques used for captopril assay require the expensive equipment and are rather time consuming. Therefore UV spectrophotometry is preferable due to its accuracy, sensitivity and simplicity. The aim of this study was to develop and validate a new, simple, rapid, precise and accurate UV spectrophotometric method for the quantitative determination of captopril in suppositories and nasal gel. Materials and methods. The objects of the study were the new drug formulations of captopril, namely 0,05 suppositories and 2,5% nasal gel developed by the scientists of The Chair of Technology of Drugs ofZaporozhye State Medical University. Distilled water was used as the solvent, working standard sample of captopril was used as a reference standard. Analytical equipment: spectrophotometer Specord 200, electronic balance ABT-120-5DM, measuring glassware of class A. Assay procedure: An accurately weighed sample of gel (0,4000 -0,8000 g) or one suppository was dissolved in distilled water and filtered into a volumetric flask (50,00 ml for gel and 250,0 ml for suppository) . Then the solution was brought to the mark with the same solvent and stirred. 1,00 ml of the resulting solution was transferred into a 25,00 ml volumetric flask and brought to the mark with distilled water. Absorbance was measured at a wavelength of 203 nm on the blank of a solvent. The parallel measurement with 1,00 ml of 0,03% captopril standard solution was carried out. The content of active substance was calculated according to standard formulas. Results. The suggested procedure was successfully applied for the analysis of two new pharmaceutical formulations. The results obtained by applying the proposed method were statistically analyzed. Validation of the method confirmed its proper precision and recovery (for gel: 100,2%, RSD% = 0,572, n = 9; for suppositories: 99,87%, RSD% = 0,420, n = 9), linearity (for gel: r =0,9978, n=6; for suppositories: r =0,9982, n=6) The received parameters enable the developed procedure to be used in quantitative pharmaceutical analysis. Conclusions. The applicability of the new procedure is well established by the assay the new drug formulations of captopril - 0,05 suppositories and 2,5% nasal gel. The developed UV spectrophotometric method is potentially useful because of its simplicity, rapidity and accuracy. The procedure is valid according to the validation requirements of Ukrainian Pharmacopeia